The Problems Affecting the Implementation of Posyandu Program: A Literature Review - Tirta Adikusuma Suparto; Nadia Nur Azizah; Septian Andriyani; Asih Purwandari Wahyoe Puspita; Yanti Hermayanti (LPPM AKPER FATMAWATI, 2022)
Integrated Health Post for Child Center/Pos Pelayanan Terpadu (Posyandu) is a form of community-based health program carried out by, from, and along with the community to empower and provide facilities for the community to obtain health services for mothers, babies, and toddlers. Posyandu activities include: KIA, family planning, immunization, nutrition, diarrhea prevention. Posyandu in Indonesia still faced several problems. This study aimed at investigating the problems that affect the implementation of Posyandu program and actions to improve Posyandu program services. The method used in this study was literature review. The literatures used in this study were the search results through national and international journals. National includes google scholar [https://scholar.google.co.id/] and international includes Pubmed [https://www.ncbi.nlm.nih.gov/pubmed] with the keyword “Problems and Posyandu Program” published in 2016-2020. Based on the search results, 8 national and 2 international articles related to the topic and in accordance with the inclusion and exclusion criteria were found. The results of 10 literature reviews show there are several fundamental problems of Posyandu program in Indonesia, namely: 1) the low role of Posyandu cadres; 2) the lack of understanding on the benefit of Posyandu program; 3) The lack of participation in Posyandu activities; 4) The lack of facilities and infrastructure for Posyandu activities; and 5) the lack of cross-program and cross-sector cooperation. In addition, there are 5 actions needed to solve the problems. The first action is to conduct a training program for Posyandu cadres. The second one is to conduct regular outreach at Posyandu for mothers and families by trained cadres. The third one is to improve the facilities and infrastructure in Posyandu. The fourth one is to provide both material and immaterial incentives for an active Posyandu’s cadre. Lastly, the fifth action is to increase advocacy efforts to related parties. Posyandu program are still facing problems affecting its implementation. Therefore, the posyandu revitalization actions are needed. The main key lies in increasing cadres' capacity through training.